Negotiating boundaries: reflections on the ethics of arts-based and artistic research in care contexts - Laukkanen Anu; Jaakonaho Liisa; Fast Heidi; Koivisto Taru-Anneli (Taylor & Francis, 2025)
BACKGROUND
Arts-based practice and research in care has increased significantly. There is a need to examine the ethical issues arising from this complex phenomenon, conceptualised as boundary work.
METHOD
To support interdisciplinary understanding in artistic and arts-based work, we collaboratively explored three arts-based research projects implemented in diverse care and healthcare contexts. The ethical issues related to boundary work were negotiated through reciprocal, in-depth reflection.
RESULTS
Arts-based and artistic research allows embodied, sensitive, and sensible encounters to emerge, in which the boundaries between artistic agency, professional positions, and even notions of evidence may be challenged. The notion of vulnerability emerges as a central ethical feature of boundary work.
CONCLUSIONS
Articulating ethical concerns in artistic-pedagogic boundary work and research can promote a more nuanced understanding of power relations in cross-sectoral practices. It may help develop services that support the agency and holistic well-being of individuals and communities.